Impact of climate change awareness on household attitude toward food waste reduction - Nwankwo-Ojionu, Chimeziem Elijah; Adzharuddin, Nor Azura; Waheed, Moniza; Mohd Khir, Azlina; Abdulwakil, Muhammad Mansur; Ehiemere, Chioma Mercy Chimeziem (Springer, 2023)
Household food waste is a significant concern beyond policy formulation and regulations because of its proximity. This study examines the impact of climate change awareness and household behavioral intentions toward food waste consequence mitigation in south-eastern Nigeria. Specifically, we evaluated complicated household attitudes, subjective norms, perceived behavioral control, and intention toward food waste in two experiments with between-subject designs: participants (N = 480), 240 (awareness, 120 aware and 120 unaware) and 240 (information, 120 high and 120 low). The first and second experiments revealed that a significant effect of climate change awareness elicited a more favorable effect on food waste reduction when households were exposed to awareness and high information banners because climate change awareness was sensitized through food waste consequences and disasters. Intention toward food waste reduction mediated the relationship between climate change awareness and food waste reduction. The theoretical and practical implications are discussed.